A Multifunctional Triphenylamine–Benzothiazole Derivative with Blue‐Shifted Mechanochromism, Acidochromism and Amplified Spontaneous Emission. Issue 3 (11th November 2020) - Fang, Bing; Lai, Liming; Chu, Manman; Shi, Yan; Yin, Meizhen
Abstract: A multifunctional triphenylamine (TPA) derivative P1 is synthesized, which contains a TPA skeleton and a benzothiazole group. P1 crystals show blue–green fluorescence and exhibit obviously blue‐shifted mechanochromism upon grinding. Analysis of crystal structures indicate that two adjacent antiparallel P1 molecules form strong intermolecular interactions and adopt a dimeric packing structure, which could be interrupted by mechanical stress, leading to blue‐shifted mechanochromism. Moreover, the proton‐donating acid effectively binds onto the benzothiazole moiety, which greatly enhances the electron‐accepting capacity of the benzothiazole moiety, leading to acidochromism with red‐shifted emission. Additionally, self‐assembled P1 microcrystals exhibit good optical waveguide features and this feature indicates P1 microcrystals serve simultaneously as gain materials and optical resonators for laser oscillation. Abstract : Acid sensitive : A multifunctional triphenylamine – benzothiazole molecule P1 was synthesized. P1 crystals show blue‐green fluorescence and exhibit blue‐shifted mechanochromism upon grinding. Moreover, a proton‐donating acid effectively binds onto the benzothiazole moiety, which greatly enhances the electron‐accepting capacity of the benzothiazole moiety, resulting in acidochromism with red‐shifted emission. Additionally, self‐assembled P1 microcrystals serve simultaneously as gain materials and optical resonators for laser oscillation.